A new genus of Thripinae (Thysanoptera, Thripidae) collected from Pandanus in Japan, Malaysia and Australia, with three new species - Masumoto, Masami; Ng, Y. F.; Okajima, Shûji (Zootaxa, 2013)
Pandanothrips gen. n. is described, with three new species inhabiting Pandanus: P. ryukyuensis sp. n. from Japan, P. wangi sp. n. from Malaysia, and P. hallingi sp. n. from Australia. This new genus shows no relationship to Projectothrips Moulton, the only other Thripinae genus known to be associated with Pandanus. Pandanothrips is superficially similar to Danothrips Bhatti, a genus of leaf feeding thrips. The morphological relationships among these genera are discussed, and an illustrated key to the species of Pandanothrips is provided.